FORECASTING THE EXCHANGE RATE OF THE IRAQI DINAR AGAINST THE US DOLLAR APPLIED RESEARCH IN THE SECONDARY MARKET (American Journal of Business Management, Economics and Banking, 2022)
The special circumstances experienced by Iraq have a great impact on the fluctuation in determining the exchange rate, so it was necessary to develop a scientific method that determines the policy of the Central Bank toward the exchange rate, and this is what we noticed after 2020 Iraq turned to an open economy and the Central Bank followed a policy to stabilize the exchange rate because of its great impact on the stability of the economy in general. Where this research was prepared to evaluate this policy towards the exchange rate by estimating the probabilities of change experienced by the exchange rate (decline, stability, and rise) by following the method of prediction and estimation of the probabilities of the causes of the occurrence of the phenomenon and through which the cases of transition from one case to another can be estimated, or to predict the state of stability of the phenomenon in the future. This research consists of two main parts, namely the theoretical side, which contains definitions, and the basis for the existing applied side, where the theoretical side contains the definition of the exchange rate, its objectives, and the factors affecting it.